Golay Complementary Sequence in the Application of Distributed Temperature Sensing System - Xiubin Sun; Xiaolian Huo (Dianxin kexue)
The value of signa1 noise ratio（SNR）is very 1ow in conventiona1 OTDR. The employed Golay complementary sequence was proposed instead of single pulse to solve that problem. By theoretica1 analysis and simulation demonstration，it was verified that this method could effectively increase the SNR.